Study of the electric field variation based on preliminary observations at the ENU cosmophysical complex in 2020 - Tulekov, Ye.; Morzabaev, А.К.; Makhmutov, V.S.; Yerkhov, V.I. (KU Publ., 2021)
The atmospheric electric field Ez is the most urgent problem of study of the physics of the atmosphere and the processes occurring in it. The conducted studies show the relationship of the electric field with atmospheric processes. Monitoring its changes is necessary to solve practical problems. This article presents brief characteristics of the installation of the EFM-100 electrostatic fluxmeter of the scientific cosmophysical experimental complex at the L.N. Gumilyov Eurasian National University (ENU) and its experimental data obtained in 2020. The article presents the results of observation of atmospheric-electrical characteristics near the Earth's surface and monitoring of the electric field of the atmosphere of the city of Nur-Sultan, in particular, estimates of the variation of the electric field of the surface layer of the atmosphere during sunrise and sunset based on data obtained by the EFM-100 fluxmeter. The comparison of meteorological data with the data of the electric field strength of the atmosphere is given. The analysis of the days and months in September and October 2020, when the conditions of “good weather” were manifested, was carried out. The series of electric field data obtained at other measuring stations show the characteristic periodicity of the electric field behavior. It is established that the value of the atmospheric electric field increases during sunrise with the manifestation of the solar terminator effect. It is interesting to study the relationship between the magnitude of the electric field of the atmosphere and the intensity of the cosmic ray flux, especially in the case of Forbush effects. The data of the ENU ground-based experimental complex allows us to conduct research on the study of atmospheric physics, including atomic electricity, as well as their interaction with cosmic rays and meto-conditions.
2020 жылғы Еуразия ұлттық университетінің Космофизикалық кешеніндегі бақылаудың алдын-ала алынған деректері бойынша электр өрісінің вариациясын зерттеу
Исследование вариации электрического поля по предварительным данным наблюдений Космофизического комплекса Евразийского национального университета в 2020 году
Keywords: cosmophysical complex; electric field variation; cosmic ray flux; electrostatic fluxmeter; electric field; solar terminator; Forbush effect; monitoring